The body in postwar Japanese fiction - Slaymaker, Douglas (Literature and society (London, England), 2004)
This book explores one of the crucial themes in postwar Japanese fiction. Through an examination of the work of a number of prominent twentieth century Japanese writers, the book analyses the meaning of the body in postwar Japanese discourse.